The Effectiveness of Using Pelvic Cushions with Different Angles on Changes in Lumbar and Cervical Lordosis a Systematic Literature Review - Neneng Rodiah; Abdul Chalik Meidian; Erry Yudhya Mulyani; Jerry Marathis (Syntax Corporation Indonesia, 2026)
Prolonged sitting in an unergonomic position has become a major concern in musculoskeletal health because it can alter physiological spinal alignment, particularly lumbar lordosis and cervical posture. Continuous static sitting may induce posterior pelvic tilt, reduce lumbar curvature, increase spinal loading, and contribute to low back pain and postural disorders. This study aimed to systematically review the effectiveness of pelvic cushions with different inclination angles in maintaining lumbar and cervical spinal alignment during sitting activities. A Systematic Literature Review (SLR) was conducted using the PRISMA framework. Relevant studies were identified from PubMed and PEDro databases through predefined keywords and Boolean operators. Articles published between 2015 and 2025 were selected based on PICOS criteria, resulting in 12 studies included for qualitative synthesis. The findings indicated that pelvic cushions and inclined seating surfaces generally improved pelvic positioning, maintained physiological lumbar lordosis, enhanced sitting comfort, and reduced biomechanical stress associated with prolonged sitting. Cushion angles ranging from approximately 10°–20° demonstrated optimal effects in supporting pelvic stability and improving load distribution. Furthermore, improvements in lumbar alignment were associated with indirect positive adaptations in cervical posture through the spinal kinetic chain mechanism. In conclusion, pelvic cushions with appropriate angle variations represent a promising ergonomic intervention for preventing postural abnormalities and musculoskeletal disorders caused by prolonged unergonomic sitting. Further research is recommended to evaluate long-term effects and direct cervical curve measurements.